The psychological impact of prosthodontic treatment: a discrete response modelling approach - Listl, Stefan (Clinical oral investigations, 2012)
Investigating the psychological impact of dental treatment is of high relevance to clinical decision makers and a promising approach for furthering patient satisfaction. This paper aims at detecting...